O que é Psicoterapia Estratégica? What is Strategic Psychotherapy? - da Veiga, Celso Lugão (IGT na Rede ISSN 1807-2526, 2004)
What it is Strategical Psycotherapy? The history of the strategical psycotherapy sends to the names of Milton Erickson, Gregory Bateson (the Bateson Project, of 1952), Don Jackson and Mental Research Institute, established in 1958, as well as the ones of Jay Haley, S. Minuchin, B. Montalvo and C. Madanés. To weave the history of the strategical psycotherapy would exceed the intention of this article; the interested reader can explore the subject in M. Elkaïm (1998). But after all, what it is strategical psycotherapy and as it is taught in the SPA of the UERJ? According to J. Haley (1991), strategical psycotherapy is any type of therapy where the therapist initiates what it happens during the therapeutical process, creating a specific methodology to approach each problem of the clinical case in question. Of this form, this methodology will include a set of destined techniques to decide the problems; if this does not occur the therapist must reevaluate its strategy until finding a strategy adequate that has led of the conflict for the solution. Ahead of everything this fits to the strategical psychotherapist to study very, to make innumerable specializations, therefore thus it will have ability to use an armory of techniques in favor of the resolution of the problems. One notices therefore that the taught strategical psycotherapy in the SPA of the UERJ, is a style that goes beyond the model considered for J. Haley (1979,1991,1993,1998) and C. Madanés (1997), but in summary harmonizes in relation the central idea of that it has a set of hypotheses on the maintenance of the problem and a set of interventions that are thought in favor of the therapeutical change. This model of performance, in terms of the Philosophy of Science, either perhaps next to a metateoria (critical study of the theories) of that a particular theory, but this already is another subject.